Congruence between nurses' and patients' assessment of postoperative pain: a literature review. (27th February 2020) - Wooldridge, Sarah; Branney, Jonathan
Abstract : Postoperative pain remains poorly managed for many patients. Effective pain management begins with accurate pain assessment, with patient self-reporting considered the most accurate measure of pain. This literature review aimed to identify how congruent nurses' assessments of pain were with patients' self-reporting. A search identified six observational studies and one quasi-experimental study that met the inclusion criteria. The findings from these studies were summarised under two themes: nurses' underestimation of patients' pain and nurses' knowledge and understanding of pain assessment. Some nurses' pain management knowledge was deemed inadequate, with evidence of negative attitudes towards managing pain in certain groups of patients. Educational interventions have so far had limited impact on correcting the ethical and professional problem of inadequate pain relief in many patients postoperatively. Randomised controlled trials are required to identify effective education interventions that can contribute to ending this avoidable suffering.